Method for manufacturing a polymer electrolyte membrane for fuel cell, membrane electrode assembly, and polymer electrolyte membrane type fuel cell - KIM HYUK; JEONG JA-HOON; LEE WON-HO; YOO HWANGAN; PARK CHEOL-HEE (2011)
The present invention relates to a method for manufacturing a polymer electrolyte membrane for a fuel cell, a membrane electrode assembly, and a polymer electrolyte membrane-type fuel cell. The method for manufacturing a polymer electrolyte membrane for a polymer electrode membrane type fuel cell of the present invention, includes the steps of (S1) forming a plurality of grooves on a base; (S2) casting an ion exchange resin solution for formation of an electrolyte membrane onto the surface of the base on which the grooves are formed; (S3) drying the ion exchange resin solution to form a polymer electrolyte membrane; and (S4) detaching the polymer electrolyte membrane formed in the previous step from the base. The ion-conductive electrolyte membrane manufactured according to the manufacturing method of the present invention has a surface with grooves for maximizing a contact area contacting a catalyst and thus enhancing performance of a cell, and improves interfacial stability with electrodes through enhanceme